2015
DOI: 10.5301/tj.5000387
|View full text |Cite
|
Sign up to set email alerts
|

Major Contributions towards Finding a Cure for Cancer through Chemotherapy: A Historical Review

Abstract: The history of cancer chemotherapy is as old as cancer itself. With the increase in the complexities of cancer and the development of resistance towards existing anticancer agents, increased attention is now being paid to the advancement of chemotherapy. Some chemotherapeutic agents were discovered by accident or trial-and-error methods while others were found to be useful for neoplasia when they were being evaluated for some other purpose. Broadly, these agents have been classified as alkylating agents, antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 93 publications
(121 reference statements)
3
30
0
Order By: Relevance
“…In conclusion, our results indicated that the administration of intraperitoneal mitomycin C, doxorubicin, cisplatin, and oxaliplatin in hyperthermic conditions did not decrease the anastomotic bursting pressure. Our observations support the importance of preclinical studies in appropriate experimental models to optimize the use of chemotherapy, which widely contributes to the cure of cancer, in spite of the advent of targeted agents (47).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In conclusion, our results indicated that the administration of intraperitoneal mitomycin C, doxorubicin, cisplatin, and oxaliplatin in hyperthermic conditions did not decrease the anastomotic bursting pressure. Our observations support the importance of preclinical studies in appropriate experimental models to optimize the use of chemotherapy, which widely contributes to the cure of cancer, in spite of the advent of targeted agents (47).…”
Section: Discussionsupporting
confidence: 77%
“…Our observations support the importance of preclinical studies in appropriate experimental models to optimize the use of chemotherapy, which widely contributes to the cure of cancer, in spite of the advent of targeted agents (47 …”
Section: Discussionsupporting
confidence: 58%
“…In the early 1900s, Paul Ehrlich started to develop drugs to treat infectious diseases, introducing the term chemotherapy. In cancer, chemotherapy works by killing or slowing down tumors by targeting dividing cells, yet nonproliferating cells are often left behind [31]. The most common drugs, nitrogen mustards, and platinum agents represent more than half of the approximately 4000 open clinical trials using DNA crosslinking agents worldwide.…”
Section: Cancer Stem Cells and Resistance To Therapymentioning
confidence: 99%
“…Cancer is one of the leading death causes in the world, with 9.6 million deaths evaluated in 2018 25 . Although enormous progress has been made in the treatment of cancer, 26 relapses linked to treatment resistance are often observed 27 . Despite the plant E. arenarium Guss was used in traditional medicine as a potent anti‐inflammatory and anti‐tumor agent, there was still little in‐depth research on the potential antitumor activities of this plant.…”
Section: Discussionmentioning
confidence: 99%